PENGARUH KUALITAS LAYANAN DAN NILAI YANG DIRASAKAN TERHADAP NIAT PEMBELIAN ULANG MELALUI MEDIASI KEPUASAN PELANGGAN RESTORAN SOLARIA DI SURABAYA - Riko Firmawan Adixio; Laila Saleh (Journal of Business & Banking, 2013)
value to customer satisfaction, which in turn are as the determinants of repurchase intention at Solaria restaurant Surabaya. Service quality refers to perception of the extent to which the services are provided with customer expectation. Customer perceived value is based on the difference between what the customer got and what customer provided for the possibility of different options. Customer satisfaction is very important to the success of the company as it is assumed to be a major driver of post purchase phenomena, such as repurchase intention. This study used non random sampling with judgemental sampling. Respondents which were selected using the consideration of an individuals ability to provide a specific type of the information needed by the research. Data were collected from 150 respondents who had visited solaria restaurant in Surabaya more than once. The method analysis used in this research was Maximum Likelihood test using the program of AMOS version 18.0. It showed some of findings namely the service quality of positively and significantly affected the customer satisfaction while perceive value did not significantly affect the customer satisfaction and, finally, customersatisfaction positively and significantly affected the repurchase intention at Solaria restaurant.